Flucytosine and Amphotericin B Coadministration Induces Dose-Related Renal Injury. Issue 2 (25th May 2017) - Folk, Alexandra; Balta, Cornel; Herman, Hildegard; Ivan, Alexandra; Boldura, Oana Maria; Paiusan, Lucian; Ardelean, Aurel; Hermenean, Anca
Invasive fungal infections remain an important clinical problem, and despite recent approaches, they bring high morbidity and mortality. Combination therapies are the most effective; however, adverse effects need to be considered. In this study, we aimed to evaluate the nephrotoxicity induced by combined therapy of flucytosine (FL) and amphotericin B (AMF) at 3 different doses administered to mice for 14 days: 300 μg/kg AMF+50 mg/kg FL; 600 μg/kg AMF+100 mg/kg FL; 900 μg/kg AMF+150 mg/kg FL. Antifungal coadministration triggered nuclear translocation of NF-κB and upregulated nuclear factor kappa-light-chain-enhancer of activated B cells subunit p65 (NF-κB p65) messenger RNA mRNA level in dose-dependent manner. The immunopositivity of tumor necrosis factor-α and interleukin-6 (IL-6), together with IL-6 gene expression, increased both in tubular and glomerular cells. Amphotericin B–flucytosine cotreatment increased significantly the number of terminal deoxy-nucleotidyl transferase (TdT)-mediated dUTP nick end-labeling positive nuclei. Apoptotic cells in renal tubuli were confirmed by electron microscopy. Histopathological analysis revealed collagen accumulation at the glomerular level. Collagen was also evidenced in the glomeruli at the dose of 900 μg/kg AMF+150mg/kg FL by Masson-Goldner trichrome staining and electron microscopy. Moreover, antifungal cotherapy induced upregulation of transforming growth factor beta 1 (TGF-β1) gene expression in a dose-dependent manner. Inflammation and epithelial tubular apoptosis are associated with TGF-β1 activation and initiation of the early stage of glomerular fibrosis at higher doses, leading to tubule–interstitial fibrosis.